EVALUATION OF COMMUNITY COMMUNITY SERVICES AND MEDIATION SERVICES INFRINGEMENT OF CHILDREN'S RIGHTS IN THE COMMISSION OF INDONESIAN CHILD PROTECTION - Naswardi Naswardi (Program Studi S3 Ilmu Manajemen, 2017)
This study aimed to evaluate the service programs of public complaints and mediation of dispute child rights violations in the Indonesian child protection commission (KPAI) . Evaluation model used was Discrepancy Evaluation Model (DEM). This study used a qualitative approach. Data collected through observation, interviews, focus groups and internal supporting data. The results showed that the sub-focus research on the Desain of the program resulted in a Skor value of three, it’s means lower inequality. This illustrates that the Desain of the program has been good. Sub focus of the program installation Skord eight, it’s means inequality are quite low and illustrates quite well the installation program. Sub focus on the process of implementing the program generates a Skor value of ten, it’s means that inequality is high enough and illustrates that the process of program implementation should be improved both from the aspect of organization, management of human resources and services. Sub focus of product produces a value of ten, it’s means that high inequality. This illustrates that the product of service complaints and dispute mediation and child rights violations in KPAI, in need of repair and upgrading. This study found some substantial weaknesses in the implementation of the program by KPAI. Limited human resources, organizational structure ineffective, limited information service system, the absence of a quality management system in service and availability of facilities, infrastructure and facilities that have not been friendly for users of the service. This is a major problem that must be corrected to improve the quality of public complaints service program of and mediation of dispute child rights violations in KPAI. Keywords:Evaluation, Program, Service, Complaint, Mediation, Dispute, Violation of Childs Right